Fetomaternal outcome in pregnancy with oligohydramnios - Modi, Jay Y.; Patel, Rina V.; Shah, Parul T.; Agrawal, Amish G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Oligohydramnios has been correlated with increased risk of FGR, meconium aspiration, birth asphyxia, low APGAR scores and congenital anomalies. Early detection of oligohydramnios and its management may help in reduction of perinatal morbidity and mortality. The aim and objectives of the study was to study the effect of oligohydramnios on fetal outcome in form of FGR, fetal distress, altered APGAR scores, NICU admission and early neonatal morbidity and mortality and to study maternal morbidity in the form of operative delivery and induced labour. Methods: 100 patients in third trimester of pregnancy with oligohydramnios confirmed by ultrasound measurement of AFI were selected randomly after satisfying inclusion and exclusion criteria. Results: Incidence of oligohydramnios and operative intervention for the same was seen more in primipara (52%). Most common causes of oligohydramnios were idiopathic (52%) followed by PIH (25%). Operative morbidity was highest in PIH (60%). Most common indication of caesarean section was fetal distress due to cord compression or FGR. 7% patients had fetoplacental insufficiency on Doppler study. Conclusions: Oligohydramnios demands intensive fetal surveillance and proper antepartum and intrapartum care. Due to high rates of intrapartum complications, perinatal morbidity and mortality, rates of caesarean section are rising, but decision between vaginal delivery and caesarean section should be well balanced so that unnecessary operative morbidity is prevented without jeopardizing the fetal well-being.